Differential elicitation of two processing proteases controls the processing pattern of the trypsin proteinase inhibitor precursor in Nicotiana attenuata - Horn, Martin; Patankar, Aparna G; Zavala, Jorge A; Wu, Jianqiang; Dolecková-Maresová, Lucie; Vujtechová, Milana; Mares, Michael; Baldwin, Ian T (Plant physiology, 2005)
Trypsin proteinase inhibitors (TPIs) of Nicotiana attenuata are major antiherbivore defenses that increase dramatically in leaves after attack or methyl jasmonate (MeJA) elicitation. To understand the elicitation process, we characterized the proteolytic fragmentation and release of TPIs from a multidomain precursor by proteases in MeJA-elicited and unelicited plants. A set of approximately 6-kD TPI peptides was purified from leaves, and their posttranslational modifications were characterized. In MeJA-elicited plants, the diversity of TPI structures was greater than the precursor gene predicted. This elicited structural heterogeneity resulted from differential fragmentation of the linker peptide (LP) that separates the seven-domain TPI functional domains. Using an in vitro fluorescence resonance energy transfer assay and synthetic substrates derived from the LP sequence, we characterized proteases involved in both the processing of the TPI precursor and its vacuolar targeting sequence. Although both a vacuolar processing enzyme and a subtilisin-like protease were found to participate in a two-step processing of LP, only the activity of the subtilisin-like protease was significantly increased by MeJA elicitation. We propose that MeJA elicitation increases TPI precursor production and saturates the proteolytic machinery, changing the processing pattern of TPIs. To test this hypothesis, we elicited a TPI-deficient N. attenuata genotype that had been transformed with a functional NaTPI gene under control of a constitutive promoter and characterized the resulting TPIs. We found no alterations in the processing pattern predicted from the sequence: a result consistent with the saturation hypothesis.
Keywords: Nicotiana; Plant Leaves; Cyclopentanes; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; inhibitory proteas; regulace genové exprese enzymů; Molecular Sequence Data; Peptide Hydrolases; molekulární sekvence - údaje; geneticky modifikované rostliny; regulace genové exprese u rostlin; posttranslační úpravy proteinů; listy rostlin; Protein Processing, Post-Translational; cyklopentany; Gene Expression Regulation, Plant; acetáty; Amino Acid Sequence; oxylipiny; Oxylipins; Plants, Genetically Modified; Enzyme Stability; rostlinné proteiny; tabák; Hydrogen-Ion Concentration; Plant Proteins; Gene Expression Regulation, Enzymologic; Acetates; Protein Precursors; koncentrace vodíkových iontů; proteinové prekurzory; Protease Inhibitors; proteasy; stabilita enzymů; sekvence aminokyselin